A Machine Learning Approach to Differentiate Cold and Hot Syndrome in Viral Pneumonia Integrating Traditional Chinese Medicine and Modern Medicine: Machine Learning Model Development and Validation - Xiaojie Jin; Yanru Wang; Jiarui Wang; Qian Gao; Yuhan Huang; Lingyu Shao; Jiali Zhao; Jintian Li; Ling Li; Zhiming Zhang; Shuyan Li; Yongqi Liu (JMIR Medical Informatics, 2025)
Abstract BackgroundSyndrome differentiation in traditional Chinese medicine (TCM) is an ancient principle that guides disease diagnosis and treatment. Among these, the cold and hot syndromes play a crucial role in identifying the nature of the disease and guiding the treatment of viral pneumonia. However, differentiating between cold and hot syndromes is often considered esoteric. Machine learning offers a promising avenue for clinicians to identify these syndromes more accurately, thereby supporting more informed clinical decision-making in the treatment. ObjectiveThis study aims to construct a diagnostic model for differentiating cold and hot syndromes in viral pneumonia by integrating TCM and modern medical features using machine learning methods. MethodsThe application of 8 machine learning algorithms (gradient boosting machine [GBM], logistic regression, random forest, extreme gradient boosting [XGB], light gradient boosting machine [LGB], ridge regression, least absolute shrinkage and selection operator, and support vector machine) generated and validated (both internally and externally) a model for differentiating cold and hot syndromes in viral pneumonia, based on clinical data from 1484 patient samples collected at 2 medical centers between 2021 and 2022. ResultsThe GBM model, which combines TCM and modern medicine features, outperformed models using only TCM features or only modern medicine features in distinguishing cold and hot syndromes in patients with viral pneumonia. The optimal discrimination model comprised 13 optimal features (temperature, red cell distribution width-SD, creatinine, total bilirubin, globulin, C-reactive protein, unconjugated bilirubin, white blood cell, neutrophil percentage, aspartate transaminase/alanine transaminase, total cholesterol, thrombocytocrit, and age) and the GBM algorithm, achieving an area under the curve (AUC) of 0.7788. Under internal and external testing, the AUCs were 0.7645 and 0.8428, respectively. Moreover, significant differences were observed between the cold and hot syndrome groups in temperature (PPPPPP ConclusionsThis pioneering study integrates the theory of TCM cold and hot syndromes with modern laboratory-based tests through machine learning. The developed model offers a novel approach for differentiating cold and hot syndromes in viral pneumonia, enabling practitioners to identify the syndrome quickly and efficiently, thereby supporting more informed clinical decision-making. Additionally, this research provides new insights into the modernization and scientific interpretation of TCM syndrome differentiation.